2009
DOI: 10.1111/j.1475-097x.2009.00872.x
|View full text |Cite
|
Sign up to set email alerts
|

Intensity of Nordic Walking in young females with different peak O2 consumption

Abstract: The purpose of this cross-sectional study was to determine the physiological reaction to the different intensity Nordic Walking exercise in young females with different aerobic capacity values. Twenty-eight 19-24-year-old female university students participated in the study. Their peak O2 consumption (VO2 peak kg(-1)) and individual ventilatory threshold (IVT) were measured using a continuous incremental protocol until volitional exhaustion on treadmill. The subjects were analysed as a whole group (n = 28) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
1
6
1
Order By: Relevance
“…So far 16 randomized (1,062 participants) and 11 observational studies (831) of Nordic Walking have been carried out. These studies have confirmed the positive effects of Nordic Walking on resting cardiac activity, arterial blood pressure, exercise tolerance, exercise oxygen consumption and quality of life in the course of various diseases of young 13 ) , middle-aged 14 ) and elderly persons 8 , 15 , 16 , 17 ) . It was confirmed that this model of rehabilitation, in particular the supervised one 5 ) , extends the walking distance of patients suffering from atherosclerosis in the lower extremities 18 ) , improves the fitness of patients suffering from Parkinson’s disease 19 , 20 ) , reduces low back pain 5 , 21 ) , symptoms of depression 22 ) and fibromyalgia 23 , 24 ) , improves the quality of sleep, reduces body weight, improves exercise tolerance and attenuates risk factors.…”
Section: Introductionsupporting
confidence: 54%
“…So far 16 randomized (1,062 participants) and 11 observational studies (831) of Nordic Walking have been carried out. These studies have confirmed the positive effects of Nordic Walking on resting cardiac activity, arterial blood pressure, exercise tolerance, exercise oxygen consumption and quality of life in the course of various diseases of young 13 ) , middle-aged 14 ) and elderly persons 8 , 15 , 16 , 17 ) . It was confirmed that this model of rehabilitation, in particular the supervised one 5 ) , extends the walking distance of patients suffering from atherosclerosis in the lower extremities 18 ) , improves the fitness of patients suffering from Parkinson’s disease 19 , 20 ) , reduces low back pain 5 , 21 ) , symptoms of depression 22 ) and fibromyalgia 23 , 24 ) , improves the quality of sleep, reduces body weight, improves exercise tolerance and attenuates risk factors.…”
Section: Introductionsupporting
confidence: 54%
“…Therefore, performing a weak style NW rather that the suggested technique could decrease the efficacy of training program. This can be relevant when fit people perform NW; indeed it has been demonstrated that Nordic walking on flat surface is not intense enough to reach high training zone in young and fit subjects [ 34 ]. When subjects were asked to use Nordic poles by keeping the arms extended the pattern of arm motion resemble those of other pole walking technique in which, a higher arm position, and a continuous hand grip is suggested [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…METs used to calculate the dose of physical activity in the NW and RT groups were compatible with previous studies. The intensity of NW has been reported to vary between 4.5 and 11.2 METs, depending on the walking speed, slope, or pole length (Hansen & Smith, ; Jurimae et al., ; Schiffer et al., , ). The majority of previous studies have been done with healthy, young, and physically active women, which may explain some of the higher METs than in the present study.…”
Section: Discussionmentioning
confidence: 99%